AB1354 Observed dosing and refill compliance in bio-naÏve and bio-experienced ankylosing spondylitis patients treated with golimumab. (23rd January 2014) - Ellis, L.; Haas, S.; Bolge, S.; Tandon, N.
Abstract : Background: Golimumab is a once-monthly, subcutaneously-administered, anti-TNF agent indicated for treatment of patients with ankylosing spondylitis (AS). Real-world dosing and refill compliance patterns of golimumab use in AS patients have not been reported previously. Objectives: This study reports golimumab (GLM) dosing and refill compliance observed in ankylosing spondylitis (AS) patients. Methods: This retrospective database analysis assessed GLM use in adult AS patients with ≥2 GLM prescriptions between 4/24/2009 and 12/31/2010; ≥1 AS diagnosis during the study period; continuous activity in the Source® LX database (≥6 months before; ≥6 months after the index GLM prescription); and a 28-31 day GLM supply. Refill compliance was defined as refills occurring ± 1 week of the expected 28-31 day (d) interval. The percent of compliant GLM refill intervals and the percent of patients demonstrating refill compliance at the 6th GLM dose were assessed in the overall population and in bio-naïve/bio-experienced subgroups. Descriptive statistics were used to characterize the study population (mean±SD, median, n and %). Results: A total of 99 AS patients and 559 GLM refill intervals were studied. The sample was 53% male; mean age of 44 years with 72% bio-experienced. A 50 mg GLM dose was found in 99% of all fills. The mean ± SD refill interval for the overall population was 35.1±21.0 d with a median of 30 d. The refill interval of bio-experienced patients (34.8±18.7 d; median 30 d) was similar to bio-naïve patients (35.8±25.8 d; median 31 d). Refill compliance was observed in 79% of all intervals for the overall population. Refill compliance at the 6th GLM dose was achieved by 83% of patients overall. Conclusions: In this retrospective analysis of a large national administrative claims database, 99% of GLM doses were 50 mg with approximately once monthly refill intervals. Overall refill compliance was observed in nearly 80% of all GLM refills and in greater than 80% of AS patients at the sixth GLM dose. Median refill interval and refill compliance appeared similar in bio-experienced and bio-naïve subgroups. Further study of these trends using additional data sources are desired to substantiate these preliminary findings. Disclosure of Interest: L. Ellis Employee of: Janssen Scientific Affairs, LLC, S. Haas Consultant for: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, N. Tandon Employee of: Janssen Scientific Affairs, LLC